Novel corrosion process applying plasma cleaning technology and four-stage attenuation current hole-forming technology
Through plasma cleaning and four-stage attenuation current hole generation technology, the problems of uneven pore diameters and excessive ineffective small holes in corroded aluminum foil are solved, and corroded foil with high specific capacitance and high mechanical strength are achieved, which is suitable for the production of high-capacity capacitors.
Patent Information
- Application Number
- CN202311408389.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
When the prior art corrodes aluminum foil, the pore size is uneven and there are too many ineffective small holes, resulting in a low capacitor capacitance, affecting application and development.
Plasma cleaning technology is used to remove impurities on the surface of aluminum foil, improve surface activity, and control the pore size and distribution of etching holes through the four-stage attenuation current hole generation technology, and optimize the pore current curve to reduce the formation of invalid holes.
It improves the specific capacity and mechanical strength of corrosive foil, ensures the consistency of product quality, enhances the bending performance of aluminum foil, reduces waste liquid generation, and is suitable for large-scale production.
Smart Images

Figure BDA0004517332600000131 
Figure HDA0004517332610000011 
Figure HDA0004517332610000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of etching foil manufacturing, in particular to a new etching process using a plasma cleaning technology and a four-level decay current pore-forming technology. Background Art
[0002] The prosperity of the electronics industry has driven the development of the electronic information industry. People's demand for medium and high-end electrolytic capacitor corrosion-formed foils is increasing, which has also led to a supply shortage in the electrolytic capacitor corrosion-formed foil market. In order to meet the development of the electronic information industry, people urgently require that the specific capacitance of electrolytic capacitors continue to increase.
[0003] Etched foil is made of electronic light foil as raw material. Through electrochemical etching method, holes are formed inwardly in the electronic light foil, thereby expanding the effective area and forming a higher specific capacity. In the process of forming holes, due to the uneven surface activity of aluminum foil and the influence of corrosion pore factors, short holes and invalid small holes will be formed, resulting in reduced capacity, affecting the application and development of etched foil. Anode foil for aluminum electrolytic capacitors must be anodized to form a certain thickness of voltage-resistant dielectric oxide film. If the diameter of the etched hole on the surface of the aluminum foil is too small, the oxide film produced during the anodization process will fill the entire etched hole, making it impossible for the working electrolyte to penetrate into the etched hole, thereby failing to achieve an effective surface expansion effect. Therefore, it is required that the pore size of the etched hole is greater than a certain critical value, so that there is enough space in the etched hole after formation as a conductive path for the working electrolyte. Only in this way can the purpose of increasing the specific capacity of the capacitor be achieved while meeting the working voltage requirements. How to increase the specific capacity of etched aluminum foil is the key technical difficulty of anodizing anode foil.
[0004] The electrolytic corrosion process of medium and high voltage aluminum foil generally includes pretreatment, pore corrosion, hole expansion corrosion, and post-treatment. The formation of uniformly distributed high-density tunnel holes with reasonable size (aperture, hole length) on the surface of aluminum foil is the key to obtaining high specific capacitance. The role of pretreatment is to remove oil, impurities and oxide film on the surface of the plain foil, improve the surface state, and promote the formation of uniformly distributed tunnel holes in the next step of pore corrosion of the aluminum foil; the role of pore corrosion is to form initial tunnel holes with a certain length and aperture on the surface of the aluminum foil by applying direct current; hole expansion corrosion is to further anodic corrosion on the basis of the initial tunnel hole, so that the aperture of the tunnel hole is further expanded to the required size to avoid the tunnel hole being blocked by the oxide film during formation; the main role of post-treatment is to eliminate the metal impurities, aluminum phosphate film and residual chloride ions inside the etched holes remaining on the surface of the aluminum foil.
[0005] In the prior art, domestic peers have relevant technical achievements and patent disclosures. The pretreatment basically uses a strong acid solution, and there is a large amount of waste liquid that needs to be treated. The methods for improving the performance of the corrosion foil disclosed in domestic patents mainly focus on the optimization of production equipment, the addition of additives to the bath solution, the improvement of the surface treatment conditions of the electronic light foil before the pore corrosion, the addition of intermediate treatment or heat treatment post-treatment steps, etc., and there are few studies and improvements on the pore current used in the pore corrosion. However, the pore current used in the pore corrosion step has a decisive effect on the density of the corrosion tunnel holes, the uniformity of the hole distribution, the hole length and the hole length uniformity. At present, the most common method in China is to use constant current corrosion to produce holes. During the pore corrosion process, due to the large current value applied, the aluminum foil is always in the process of hole initiation and hole growth during the entire period of power-on, and the uniformity of the length of the pores in the obtained corrosion foil tunnel is poor. In addition, since the aluminum foil is always in a pore state when the constant current pore corrosion is used, the number of invalid short holes generated later increases, and a large number of parallel holes are formed on the surface of the aluminum foil, resulting in the thinning of the aluminum foil, which reduces the mechanical strength of the electrode foil. A decay current curve is disclosed in the patent document with the announcement number CN111733443A. The decay current waveform is as follows: Figure 1 As shown, a corrosion foil with high specific capacitance and high mechanical strength for a formation voltage of 500V or more can be prepared. The use of this decay current curve can reduce the generation of new holes to a certain extent in the late stage of power-on, but there is still a certain degree of new hole initiation in the process from the late stage of current decay to the end constant current. This part of the tunnel holes induced in the late stage of power-on will eventually form tunnel holes with small aperture and short hole length. After the formation step, there is a possibility of being blocked, and it does not contribute to the specific capacitance of the corrosion foil. The use of this decay current curve does not have sufficient control over the aperture of the pores in the early stage of power-on, and the uniformity of the aperture distribution is poor. Summary of the invention
[0006] The purpose of the present invention is to provide a new etching process using plasma cleaning technology and four-level attenuation current pore-forming technology. The medium and high voltage electronic aluminum foil prepared by the process has the characteristics of higher product quality consistency, good bending performance and high capacity, and is simple to operate and has good production effect.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A new etching process using plasma cleaning technology and four-level decay current pore generation technology, the process includes the following steps:
[0009] (1) Pretreatment: Placing high-purity aluminum foil in a plasma device for plasma cleaning to remove surface impurities and improve surface activity;
[0010] (2) Primary pore etching: The foil cleaned in step (1) is placed in a primary pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75° C. and a direct current of a special current curve; the primary pore etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0011] (3) Primary chemical etching: The foil treated in step (2) is placed in a primary chemical etching solution and immersed at 65-75° C. for 0.5-1 min. The primary chemical etching solution comprises: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0012] (4) Secondary pore etching: The foil after primary chemical etching is placed in a secondary pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75°C and a direct current of a special current curve; the composition of the secondary pore etching solution is: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0013] (5) Secondary chemical etching: The foil treated in step (4) is placed in a secondary chemical etching solution and immersed at 65-75° C. for 0.5-1.0 min; the secondary chemical etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0014] (6) Three-stage pore etching: The foil after secondary chemical etching is placed in a three-stage pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75°C and a direct current of a special current curve; the three-stage pore etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0015] (7) Three-time chemical etching: The foil treated in step (6) is placed in a three-time chemical etching solution and immersed at a temperature of 65-75° C. for 0.5-1.0 min; the three-time chemical etching solution comprises: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0016] (8) Four-stage pore etching: The foil after three electrochemical etchings is placed in a four-stage pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75°C and a direct current condition of a special current curve; the four-stage pore etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0017] (9) Four-time chemical etching: the foil treated in step (8) is placed in a four-time chemical etching solution and immersed at a temperature of 65-75° C. for 0.5-1.0 min; the four-time chemical etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water;
[0018] (10) Hole expansion corrosion: The aluminum foil treated in step (9) is washed with water and then placed in a hole expansion solution for secondary direct current electric hole expansion corrosion, wherein the hole expansion solution is composed of 8 to 12 wt.% nitric acid, 0.2 to 0.5 wt.% sodium dodecylbenzene sulfonate, and the balance is water; the current is applied for 200 to 500 s in the secondary direct current electric hole expansion corrosion, the current density is 50 to 500 mA / cm2, and the corrosion temperature is 70 to 90°C;
[0019] (11) Post-treatment and drying.
[0020] The plasma cleaning process in the above step (1) is as follows: the aluminum foil is cleaned by using a radio frequency plasma cleaning machine, wherein at least two plasma generators are provided in the radio frequency plasma cleaning machine, and the plasma generators are simultaneously provided on the front and back sides of the aluminum foil, and argon gas is introduced into the plasma generator as a cleaning gas, so that a clean aluminum foil surface is obtained after cleaning; the plasma cleaning process is environmentally friendly and energy-saving, and the decontamination is thorough and fast, and the mechanical properties of the aluminum foil can be guaranteed.
[0021] Preferably, the RF plasma cleaning process parameters are: air pressure 0.1-0.4MPa, power density 0.5-3W / CM 2 , RF frequency 13.56MHZ-27.12MHZ, cleaning time 1-3 minutes, gas flow 80-110ml / min, cleaning temperature 35-45℃.
[0022] Preferably, the special current curve in each level of pore corrosion is specifically:
[0023] In the time period from 0 to t1, a large current is applied for a short time with a constant current, and the current density is I1; in the time period from t1 to t2, the current density is reduced from I1 to I2 by decreasing the power supply, and the curve equation of the current density is y=-lnx+b, where y is the current density and x is the time; a small current density is used at time t2 to t3, and the curve equation of the current density is y=kx, where y is the current density, x is the time, and k<0, and the current density is reduced from I2 to I3; the current density I1>I2>I3, and the current density I1 is 1.0~3.8A / cm 2 , the current density I2 = 0.20 ~ 1.0A / cm 2 The current density I3 is 0.05-0.2A / cm 2 .
[0024] The t1 is 0.5-1.0s, the t1-t2 time period is 6-8s, and the t2-t3 time period is 11-13s; the total power-on time for each level of pore corrosion is 18-22s, and the total current is 1900-2500A; the pore corrosion is divided into four levels, and the aluminum content and temperature control of the bath solution increase step by step.
[0025] The post-treatment process of step (11) is as follows: the aluminum foil treated in step (10) is washed with water and then immersed in an acid treatment solution, wherein the acid treatment solution comprises 2-5 wt.% nitric acid, 0.10-0.25 mol / L Al 3+ , the rest is water; in the post-treatment, the immersion time is 100 to 200 seconds, and the temperature of the acid treatment solution is 55 to 75°C.
[0026] The drying process of the above step (11) is: the post-treated aluminum foil is cleaned with pure water, and then the etched foil is dried and rolled up; the drying conditions are: the temperature is 120-300°C, and the processing time is 1-2.5 minutes, so that the ultra-high capacity etched foil is obtained.
[0027] The process of the present invention can produce anode foil with specifications of 250-850Vf. The prepared corrosion foil has a specification of 640Vf and a capacity of up to 0.61μF / cm 2 , specification 250Vf capacity can reach 2.55μF / cm 2 .
[0028] The design principle and beneficial effects of the present invention are as follows:
[0029] 1. The etching process of medium- and high-voltage etching foil for high-capacity and high-strength capacitors provided by the present invention includes the use of plasma cleaning to prepare aluminum foil with a clean surface, improve the surface activity of the aluminum foil, and increase the uniformity of pore formation. It also includes the use of a current curve with a special waveform, using a large current and a short-time constant current to form pores in the front stage of power-on, enhancing the control of the pore diameter in the pore formation stage, and improving the consistency of the pore diameter; in the back stage of power-on, according to the requirements of the pore diameter for different product specifications, design a current curve suitable for the high-voltage section and the medium-voltage section, further enhance the control of the pore size, and reduce the dispersion of product capacity. This kind of electronic aluminum foil has the characteristics of high bending, high capacity and higher consistency; this kind of electronic aluminum foil is suitable for the use environment where the anode aluminum foil of electrolytic capacitors cannot meet the high-capacity and high-bending requirements on the market. At the same time, the production method is simple, the process quality is easy to control, and the production method is suitable for mass production in large enterprises.
[0030] 2. The corrosion process of the medium- and high-voltage electronic aluminum foil for high-capacity and high-strength capacitors described in the present invention: by using plasma to clean the aluminum foil, the activity and pore uniformity of the aluminum foil surface can be effectively enhanced, the formation of short corrosion holes can be avoided or reduced, and the capacity index of the product can be improved without reducing the mechanical properties; at the same time, the generation of waste liquid can be reduced and related investment can be avoided.
[0031] 3. The present invention optimizes the hole-generating current curve. The first stage uses a large current for a short time to generate holes, which is conducive to controlling the initiation of corrosion tunnel holes; the second stage uses a decreasing current to control the growth of corrosion tunnel holes and avoid or reduce the formation of invalid small holes; the third stage uses a small current for a short time to expand holes, which is conducive to controlling the aperture size. Different current curves are used for products of different specifications to obtain corresponding numbers and aperture sizes of corrosion holes, thereby improving product capacity.
[0032] 4. The present invention can improve the consistency of the aperture of the anode foil product through four-stage aperture. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the current curve 1 of the existing comparative example 1.
[0034] Figure 2 This is the special current curve 2 of Example 1.
[0035] Figure 3 This is the special current curve 3 of Example 2. DETAILED DESCRIPTION
[0036] In order to further understand the present invention, the present invention is described below in conjunction with examples, but the examples are only for further elaboration of the features and advantages of the present invention, rather than for limiting the claims of the present invention.
[0037] High-voltage aluminum foil belongs to the category of electronic aluminum foil. It is a corroded material that works under polar conditions. Electronic aluminum foils of different voltage ranges require different types of corrosion. High-voltage anode foils are generally columnar tunnel-shaped corrosion structures, because when working under high voltage, they need to have a relatively thick oxide film that is resistant to high voltage, but this thick oxide film cannot block the corrosion holes generated during corrosion production, otherwise it will cause a decrease in specific capacitance. In order to simultaneously meet the two conditions that high-voltage anode foils should have thicker oxide films and larger specific capacitance, generating as many effective etching holes as possible is the best choice to increase product capacity.
[0038] At present, the anode aluminum foil of electrolytic capacitors produced domestically cannot meet the performance requirements of high capacity and high bending in the market, especially in the Japanese high-end corrosion foil market, which mainly uses anode aluminum foil for high-voltage electrolytic capacitors produced in Japan.
[0039] In order to solve the above problems, the present invention provides a new corrosion process using plasma cleaning technology and four-level decay current pore generation technology. The present invention adopts plasma cleaning technology to prepare aluminum foil with a clean surface, improve the surface activity of the aluminum foil, and increase the uniformity of pore generation. The present invention adopts a special pore generation current curve. The front section of the curve is a short-term large current constant current pore generation, which modulates the number and size of the apertures; the middle section of the curve is a decay current, which promotes the growth of the corrosion pits; the back section of the curve is a small current long-term constant current pore expansion, which effectively modulates the aperture size. This type of electronic aluminum foil has more pores and higher pore consistency, which not only ensures the mechanical properties of the anode aluminum foil, but also provides the corrosion area of the electronic aluminum foil to the greatest extent, solving the contradiction between the specific capacitance and its mechanical properties during the corrosion process of the electronic aluminum foil.
[0040] In the following examples, Al 3+ The source is aluminum nitrate.
[0041] Embodiment 1:
[0042] This embodiment designs a special pore current curve for high voltage section corrosion foil products ( Figure 2 ), with the characteristics of larger pore size, fewer number and higher capacity. The details are as follows:
[0043] (1) Pretreatment: Place the high-purity aluminum foil in a plasma device for plasma cleaning to remove surface impurities and enhance surface activity. Specifically: Use a radio frequency plasma cleaning machine to clean the aluminum foil. The radio frequency plasma cleaning machine is equipped with at least two plasma generators, and the plasma generators are simultaneously arranged on the front and back of the aluminum foil. Argon gas is introduced into the plasma generator as a cleaning gas, and a clean aluminum foil surface is obtained after cleaning. The plasma cleaning process is environmentally friendly and energy-saving, and the decontamination is thorough and fast, and the mechanical properties of the aluminum foil can be guaranteed. The radio frequency plasma cleaning process parameters are: air pressure 0.14MPa, power density 1.3W / CM 2, RF frequency 13.56MHZ, cleaning time 2 minutes, gas flow 100ml / min, cleaning temperature 40℃.
[0044] (2) Primary pore etching: The cleaned foil is placed in a primary pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 68-68.5°C and a direct current of a special current curve; the composition of the primary pore etching solution is: 0.860 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.18 mol / L Al 3+ , and the rest is water.
[0045] (3) Primary chemical etching: The foil treated in step (2) is placed in a primary chemical etching solution and soaked for 0.6 min at a temperature of 68-68.5° C. The primary chemical etching solution comprises: 0.860 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, and 0.15-0.20 mol / L Al 3+ , and the rest is water.
[0046] (4) Secondary pore etching: The foil after the primary chemical etching is placed in a secondary pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 68.5-69.0°C and a direct current of special current curve 2; the composition of the secondary pore etching solution is: 0.860 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.20-0.25 mol / L Al 3+ , and the rest is water.
[0047] (5) Secondary chemical etching: The foil treated in step (4) is placed in a secondary chemical etching solution and immersed at 68.5-69.0°C for 0.6 min; the secondary chemical etching solution is composed of: 0.860 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.20-0.25 mol / L Al 3+ , the rest is water;
[0048] (6) Three-stage pore etching: The foil after secondary chemical etching is placed in a three-stage pore etching solution, and is immersed and corroded for 21 seconds at a temperature of 69.5-70.0°C and a direct current of special current curve 2; the three-stage pore etching solution is composed of: 0.860 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.25-0.30 mol / L Al 3+ , and the rest is water.
[0049] (7) Three-time chemical etching: The foil treated in step (6) is placed in a three-time chemical etching solution and immersed at a temperature of 69.5-70.0°C for 0.6 min; the three-time chemical etching solution comprises: 0.860 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.25-0.30 mol / L Al 3+ , and the rest is water.
[0050] (8) Four-stage pore etching: The foil after three electrochemical etchings is placed in a four-stage pore etching solution, and is immersed and corroded for 21 seconds at a temperature of 70.0-70.5°C and a direct current condition of a special current curve; the four-stage pore etching solution is composed of: 0.860 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.30-0.35 mol / L Al 3+ , the rest is water;
[0051] (9) Four-time chemical etching: The foil treated in step (8) is placed in a four-time chemical etching solution and immersed at a temperature of 70.0-70.5° C. for 0.60 min; the four-time chemical etching solution is composed of: 0.860 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.30-0.35 mol / L Al 3+ , and the rest is water.
[0052] (10) Hole expansion corrosion: The aluminum foil treated in step (9) is washed with water and then placed in a hole expansion solution for secondary direct current powered hole expansion corrosion, wherein the hole expansion solution is composed of 10 wt.% nitric acid, 0.25 wt.% sodium dodecylbenzene sulfonate, and the balance is water; the current is applied for 320 s in the secondary direct current powered hole expansion corrosion, the current density is 0.220 mA / cm2, and the corrosion temperature is 85.0°C.
[0053] (11) Post-treatment: The aluminum foil treated in step (10) is washed with water and then immersed in an acid treatment solution. The acid treatment solution is composed of 3.5 wt.% nitric acid, 0.15 mol / L Al 3+ , the rest is water; in the post-treatment, the soaking time is 120s, and the temperature of the acid treatment solution is 65°C;
[0054] (12) Drying: After the aluminum foil treated in step (11) is cleaned with pure water, it is dried and rolled up. Drying conditions: temperature is 150°C, and treatment time is 2.5 minutes. Thus, an ultra-high capacity etching foil is obtained.
[0055] In this embodiment, the pore corrosion treatment is carried out as follows Figure 2The special current curve 2 shown is specifically as follows: in the time period of 0 to t1, a large current is applied for a short time constant current, and the current density is I1; in the time period of t1 to t2, the current density is reduced from I1 to I2 by decreasing the power supply, and the curve equation of the current density is y=-lnx, where y is the current density and x is the time; a small current density is used at time t2 to t3, and the curve equation of the current density is y=kx, where y is the current density, x is the time, and k is -0.057, and the current density is reduced from I2 to I3; the current density I1>I2>I3, and the current density I1 is 1.00A / cm 2 , the current density I2 = 0.20A / cm 2 The current density I3 is 0.15 to 0.18 A / cm 2 . The t1 is 1.0s. The t1-t2 is 8s. The t2-t3 is 12s. The total power-on time for each level of pore corrosion is 21s, and the total current is 2500A. There are four levels of pore corrosion:
[0056] Through the above steps, an anode foil suitable for 550-850Vf can be prepared. The prepared corrosion foil is characterized in that the capacity of the corrosion foil at 640Vf can reach 0.61μF / cm2, the bending time is greater than 52 times, and the capacity dispersion does not exceed 3%.
[0057] Embodiment 2:
[0058] For the corrosion foil products in the medium and high voltage sections, special Figure 3 The pore current curve 3 has the characteristics of smaller pore size, greater pore number and higher capacity.
[0059] (1) Pretreatment:
[0060] Place high-purity aluminum foil in a plasma device for plasma cleaning to remove surface impurities and enhance surface activity. Specifically: A radio frequency plasma cleaning machine is used to clean the aluminum foil. The radio frequency plasma cleaning machine is equipped with at least two plasma generators, and the plasma generators are simultaneously arranged on the front and back of the aluminum foil. Argon gas is introduced into the plasma generator as a cleaning gas, and a clean aluminum foil surface is obtained after cleaning. The plasma cleaning process is environmentally friendly and energy-saving, and the decontamination is thorough and fast, and the mechanical properties of the aluminum foil can be guaranteed. The radio frequency plasma cleaning process parameters are: air pressure 0.15MPa, power density 1.6W / CM 2 , RF frequency 27.12MHZ, cleaning time 1.5 minutes, gas flow 110ml / min, cleaning temperature 35℃.
[0061] (2) Primary pore etching: The cleaned foil is placed in a primary pore etching solution, and is immersed and etched for 19 seconds at a temperature of 70-70.5°C and a direct current of special current curve 3; the composition of the primary pore etching solution is: 0.810 mol / L hydrochloric acid, 3.70 mol / L sulfuric acid, 0.20 mol / L Al 3+ , and the rest is water.
[0062] (3) Primary chemical etching: The foil treated in step (2) is placed in a primary chemical etching solution and soaked for 0.5 min at a temperature of 70.0-70.5°C; the primary chemical etching solution comprises: 0.810 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.15-0.20 mol / L Al 3+ , and the rest is water.
[0063] (4) Secondary pore etching: The foil after the primary chemical etching is placed in a secondary pore etching solution, and is immersed and corroded for 19 seconds at a temperature of 60.5-71.0°C and a direct current of the special current curve 3; the composition of the secondary pore etching solution is: 0.810 mol / L hydrochloric acid, 3.70 mol / L sulfuric acid, 0.25 mol / L Al 3+ , and the rest is water.
[0064] (5) Secondary chemical etching: The foil treated in step (4) is placed in a secondary chemical etching solution and immersed at a temperature of 70.5-71.0°C for 0.5 min; the secondary chemical etching solution is composed of: 0.810 mol / L hydrochloric acid, 3.50 mol / L sulfuric acid, 0.25 mol / L Al 3+ , the rest is water;
[0065] (6) Three-stage pore etching: The foil treated in step (5) is placed in a three-stage pore etching solution, and is immersed and corroded for 19 seconds at a temperature of 71.0-71.5°C and a direct current of special current curve 3; the three-stage pore etching solution is composed of: 0.810 mol / L hydrochloric acid, 3.70 mol / L sulfuric acid, 0.30 mol / L Al 3+ , and the rest is water.
[0066] (7) Three-time chemical etching: The foil treated in step (6) is placed in a three-time chemical etching solution and immersed at a temperature of 71.5-72.0°C for 0.5 min; the three-time chemical etching solution comprises: 0.810 mol / L hydrochloric acid, 3.70 mol / L sulfuric acid, 0.35 mol / L Al 3+ , and the rest is water.
[0067] (8) Four-stage pore etching: The foil treated in step (7) is placed in a four-stage pore etching solution, and is immersed and corroded for 19 seconds at a temperature of 72.0-72.5° C. and a direct current of a special current curve; the four-stage pore etching solution is composed of: 0.810 mol / L hydrochloric acid, 3.70 mol / L sulfuric acid, 0.35 mol / L Al 3+ , the rest is water;
[0068] (9) Four-time chemical etching: The foil treated in step (8) is placed in a four-time chemical etching solution and immersed at a temperature of 72.0-72.5° C. for 0.5 min; the four-time chemical etching solution is composed of: 0.810 mol / L hydrochloric acid, 3.70 mol / L sulfuric acid, 0.35 mol / L Al 3+ , and the rest is water.
[0069] (10) Hole expansion corrosion: The aluminum foil treated in step (9) is washed with water and then placed in a hole expansion solution for secondary direct current powered hole expansion corrosion, wherein the hole expansion solution is composed of 11 wt.% nitric acid, 0.22 wt.% sodium dodecylbenzene sulfonate, and the remainder is water; the current is applied for 160 s in the secondary direct current powered hole expansion corrosion, the current density is 0.400 mA / cm2, and the corrosion temperature is 87.0°C.
[0070] (11) Post-treatment: The aluminum foil treated in step (10) is washed with water and then immersed in an acid treatment solution. The acid treatment solution is composed of 3.5 wt.% nitric acid, 0.15 mol / L Al 3+ , the rest is water; in the post-treatment, the immersion time is 120s, and the temperature of the acid treatment solution is 62°C;
[0071] (12) Drying: After the aluminum foil treated in step (11) is cleaned with pure water, it is dried and rolled up. Drying conditions: temperature is 200°C, and treatment time is 1.5 minutes. Thus, an ultra-high capacity etching foil is obtained.
[0072] The pore corrosion treatment in this embodiment adopts a special current curve 3, specifically: in the time period of 0 to t1, a large current is applied for a short time with a constant current, and the current density is I1; in the time period of t1 to t2, the current density is reduced from I1 to I2 by decreasing the power supply, and the curve equation of the current density is y=-lnx, where y is the current density and x is the time; a small current density is used at time t2 to t3, and the curve equation of the current density is y=kx, where y is the current density, x is the time, and k is -0.112, and the current density is reduced from I2 to I3; the current density I1>I2>I3, and the current density I1 is 1.50A / cm 2 , the current density I2 = 0.20A / cm2 , the current density I3 is 0.10A / cm 2 . The t1 is 1.0s. The t1-t2 is 8s. The t2-t3 is 12s. The total power-on time for each level of pore corrosion is 19s, and the total current is 2500A. There are four levels of pore corrosion:
[0073] Through the above steps, an anode foil with a specification of 250Vf can be prepared. The prepared corrosion foil has a capacity of 250Vf of up to 2.55μF / cm2, can be bent more than 52 times, and has a capacity dispersion of no more than 3%.
[0074] Comparative Example 1:
[0075] (1) Pretreatment: Treat the high-purity aluminum foil with phosphoric acid solution. Conditions: temperature 65°C, time 80 seconds, phosphoric acid concentration 2.0%; remove surface impurities, surface oil stains, and part of the oxide film to achieve the purpose of cleaning the aluminum foil surface;
[0076] (2) Primary pore etching: Place the foil after chemical cleaning in a pore etching solution, and immerse and etch for 22 seconds at a certain temperature (67°C) and direct current conditions of a special current curve; the electrochemical etching solution and the pore etching solution are both composed of 0.690 mol / L hydrochloric acid, 3.4.1 mol / L sulfuric acid, and 0.25 mol / L Al3+. The pore current curve adopts Figure 1 The pore current curve 1 is shown.
[0077] (3) Primary chemical etching: The foil after the above treatment is placed in a chemical etching solution at a certain temperature (67°C) for 0.7 minutes. The chemical etching solution and the pore etching solution are both composed of 0.690 mol / L hydrochloric acid, 3.41 mol / L sulfuric acid, and 0.25 mol / L Al3+.
[0078] (4) Secondary pore etching: Place the foil after chemical etching in a pore etching solution, and immerse and etch for 22 seconds at a certain temperature (68.0°C) and direct current conditions of a special current curve; the electrochemical etching solution and the pore etching solution are both composed of 0.690 mol / L hydrochloric acid, 3.41 mol / L sulfuric acid, and 0.30 mol / L Al3+. The pore current curve adopts Figure 1 The pore current curve 1 is shown.
[0079] (5) Secondary chemical etching: Place the foil after the above treatment in a chemical etching solution at a certain temperature (68.0°C) for 0.5-1.0 min. The electrochemical etching solution and the pore etching solution are both composed of 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, and 0.25-0.55 mol / L Al3+.
[0080] (6) Level 3 pore etching: Place the electrochemically etched foil in a pore etching solution and immerse it for 22 seconds at a certain temperature (69.0°C) and direct current conditions of a special current curve; the electrochemical etching solution and the pore etching solution are both composed of 0.690 mol / L hydrochloric acid, 3.41 mol / L sulfuric acid, and 0.35 mol / L Al3+. The pore current curve is adopted Figure 1 The pore current curve 1 is shown.
[0081] (7) Three-time chemical etching: Place the foil after the above treatment in a chemical etching solution at a certain temperature (69.0°C) for 0.5-1.0 min. The electrochemical etching solution and the pore etching solution are both composed of 0.690 mol / L hydrochloric acid, 3.4.1 mol / L sulfuric acid, and 0.35 mol / L Al3+.
[0082] (8) Level 4 pore etching: Place the foil after chemical etching in a pore etching solution, and immerse and etch for 22 seconds at a certain temperature (70.0°C) and under the direct current conditions of special current curve 1; the electrochemical etching solution and pore etching solution are both composed of 0.690 mol / L hydrochloric acid, 3.41 mol / L sulfuric acid, and 0.40 mol / L Al3+. The pore current curve adopts Figure 1 The pore current curve 1 is shown.
[0083] (9) Four times of electrochemical etching: The foil treated in step (8) is placed in an electrochemical etching solution at a certain temperature (70.0° C.) for 0.5-1.0 min. The electrochemical etching solution and the pore etching solution are both composed of 0.690 mol / L hydrochloric acid, 3.4.1 mol / L sulfuric acid, and 0.40 mol / L Al3+.
[0084] (10) Hole expansion corrosion: The aluminum foil treated in step (9) is washed with water and then placed in a hole expansion solution for secondary direct current hole expansion corrosion. The hole expansion solution is a 10% by mass nitric acid + 0.35% sodium dodecylbenzene sulfonate solution. The current is applied for 270 seconds in the secondary direct current hole expansion corrosion, and the current density is 0.34 mA / cm2. The temperature is 78°C.
[0085] (11) Post-treatment: The aluminum foil treated in step (10) is washed with water and then immersed in an acid treatment solution, wherein the acid treatment solution is a 3.0% by mass nitric acid + 0.25 mol / L Al3+ solution; in the post-treatment, the immersion time is 140 s and the temperature of the solution is 60° C.;
[0086] (12) Drying: After the aluminum foil treated in step (11) is cleaned with pure water, it is dried and rolled up. Drying conditions: temperature is 200°C, and treatment time is 1.5 minutes. The etched foil is thus obtained.
[0087] The pitting corrosion treatment in this comparative example adopts a special current curve 1, specifically: in the time period of 0 to t1, a slash-type increasing current is applied, and the current density increases from 0 to I1; in the time period of t1 to t2, a short-time constant current is applied, and the current is I2; a small current density is used at the time of t2 to t3, and the curve equation of the current density is y=kx, where y is the current density, x is the time, k<0, and the current density is reduced from I2 to I3; the current density I1=I2>I3, and the current density I1 is 2.8A / cm 2 , the current density I2 = 2.8A / cm 2 The current density I3 is 0.5-0.2A / cm 2 . The t1 is 2.0s. The t2-t1 is 2.0s. The t3-t2 is 12s. The total power-on time of each level of pore corrosion is 18s, and the total current is 1920A. The pore corrosion is divided into four levels, and the aluminum content and temperature of the bath are controlled to increase step by step.
[0088] The above steps can be used to prepare an anode foil with a specification of 200-700Vf. The prepared corrosion foil is characterized in that the capacity of the corrosion foil at 250Vf can reach 2.45μF / cm2, the bending is greater than 50 times, and the capacity dispersion is 5.2%; the 640Vf specific capacitance is 0.59μF / cm2, the bending is greater than 50 times, and the capacity dispersion is 5.2%.
[0089] The quality index data of the above embodiments and comparative examples are shown in Table 1:
[0090] Table 1
[0091]
Claims
1. A new etching process using plasma cleaning technology and four-level attenuation current pore generation technology, characterized in that: The process includes the following steps: (1) Pretreatment: Placing high-purity aluminum foil in a plasma device for plasma cleaning to remove surface impurities and improve surface activity; (2) Primary pore etching: The foil cleaned in step (1) is placed in a primary pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75° C. and a direct current of a special current curve; the primary pore etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (3) Primary chemical etching: The foil treated in step (2) is placed in a primary chemical etching solution and immersed at 65-75° C. for 0.5-1 min. The primary chemical etching solution comprises: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (4) Secondary pore etching: The foil after primary chemical etching is placed in a secondary pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75°C and a direct current of a special current curve; the composition of the secondary pore etching solution is: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (5) Secondary chemical etching: The foil treated in step (4) is placed in a secondary chemical etching solution and immersed at 65-75° C. for 0.5-1.0 min; the secondary chemical etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (6) Three-stage pore etching: The foil after secondary chemical etching is placed in a three-stage pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75°C and a direct current of a special current curve; the three-stage pore etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (7) Three-time chemical etching: The foil treated in step (6) is placed in a three-time chemical etching solution and immersed at a temperature of 65-75° C. for 0.5-1.0 min; the three-time chemical etching solution comprises: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (8) Four-stage pore etching: The foil after three electrochemical etchings is placed in a four-stage pore etching solution, and is immersed and corroded for 18-22 seconds at a temperature of 65-75°C and a direct current condition of a special current curve; the four-stage pore etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (9) Four-time chemical etching: the foil treated in step (8) is placed in a four-time chemical etching solution and immersed at a temperature of 65-75° C. for 0.5-1.0 min; the four-time chemical etching solution is composed of: 0.6-1.0 mol / L hydrochloric acid, 3.2-4.1 mol / L sulfuric acid, 0.15-0.35 mol / L Al 3+ , the rest is water; (10) Hole expansion corrosion: The aluminum foil treated in step (9) is washed with water and then placed in a hole expansion solution for secondary direct current electric hole expansion corrosion, wherein the hole expansion solution is composed of 8 to 12 wt.% nitric acid, 0.2 to 0.5 wt.% sodium dodecylbenzene sulfonate, and the balance is water; the current is applied for 200 to 500 s in the secondary direct current electric hole expansion corrosion, the current density is 50 to 500 mA / cm2, and the corrosion temperature is 70 to 90°C; (11) Post-treatment and drying.
2. The new etching process using plasma cleaning technology and four-level attenuation current pore generation technology according to claim 1 is characterized in that: The plasma cleaning process of step (1) is as follows: the aluminum foil is cleaned by using a radio frequency plasma cleaning machine, wherein at least two plasma generators are arranged in the radio frequency plasma cleaning machine, and the plasma generators are arranged on the front and back sides of the aluminum foil at the same time, and argon gas is introduced into the plasma generator as a cleaning gas, and a clean aluminum foil surface is obtained after cleaning; the plasma cleaning process is environmentally friendly and energy-saving, and the decontamination is thorough and fast, and the mechanical properties of the aluminum foil can be guaranteed.
3. The new etching process using plasma cleaning technology and four-level attenuation current pore generation technology according to claim 2 is characterized in that: The RF plasma cleaning process parameters are: gas pressure 0.1-0.4MPa, power density 0.5-3W / CM 2 , RF frequency 13.56MHZ-27.12MHZ, cleaning time 1-3 minutes, gas flow 80-110ml / min, cleaning temperature 35-45℃.
4. The new etching process using plasma cleaning technology and four-level attenuation current pore generation technology according to claim 1 is characterized in that: The special current curves described in each level of pitting corrosion are as follows: In the time period from 0 to t1, a large current is applied for a short time with a constant current, and the current density is I1; in the time period from t1 to t2, the current density is reduced from I1 to I2 by decreasing the power supply, and the curve equation of the current density is y=-lnx+b, where y is the current density and x is the time; a small current density is used at time t2 to t3, and the curve equation of the current density is y=kx, where y is the current density, x is the time, and k<0, and the current density is reduced from I2 to I3; the current density I1>I2>I3, and the current density I1 is 1.0~3.8A / cm 2 , the current density I2 = 0.20 ~ 1.0A / cm 2 The current density I3 is 0.05-0.2A / cm 2 .
5. The new etching process using plasma cleaning technology and four-level attenuation current pore generation technology according to claim 4 is characterized in that: The t1 is 0.5-1.0s, the t1-t2 time period is 6-8s, and the t2-t3 time period is 11-13s; the total power-on time for each level of pore corrosion is 18-22s, and the total current is 1900-2500A; the pore corrosion is divided into four levels, and the aluminum content and temperature control of the bath solution increase step by step.
6. The new etching process using plasma cleaning technology and four-level attenuation current pore generation technology according to claim 1 is characterized in that: The post-treatment process of step (11) is as follows: the aluminum foil treated in step (10) is washed with water and then immersed in an acid treatment solution, wherein the acid treatment solution comprises 2-5 wt.% nitric acid, 0.10-0.25 mol / L Al 3+ , the rest is water; in the post-treatment, the immersion time is 100 to 200 seconds, and the temperature of the acid treatment solution is 55 to 75°C.
7. The new etching process using plasma cleaning technology and four-level attenuation current pore generation technology according to claim 1 is characterized in that: The drying process of step (11) is as follows: the post-treated aluminum foil is cleaned with pure water, and then the etching foil is dried and rolled up; the drying conditions are: the temperature is 120-300° C., and the processing time is 1-2.5 minutes, so that the ultra-high capacity etching foil is obtained.
8. The new etching process using plasma cleaning technology and four-level attenuation current pore generation technology according to claim 1 is characterized in that: This process can produce anode foils with specifications of 250 to 850 Vf. The prepared corrosion foils have specifications of 640 Vf and a capacity of up to 0.61 μF / cm 2 , specification 250Vf capacity can reach 2.55μF / cm 2 .
Citation Information
Patent Citations
Method for manufacturing electrode foil for aluminum electrolytic capacitor and electrode foil
CN111733443A
Cited By
Medium-high voltage formed foil, preparation method thereof and aluminum electrolytic capacitor
CN120854172A
Medium-high voltage formed foil, method of making the same, and aluminum electrolytic capacitor
CN120854172B